Implementasi Marker Based Tracking pada Aplikasi Augmented Reality Batik Majalengka Berbasis Android - Deni Priyadi (Bandung Conference Series: Communication Management, 2023)
Abstract. Multimedia is a product of information technology which has the advantage of attracting imagination and attracting public interest, this attraction is supported by images, sound, text and animated movements. Batik businesses experience several obstacles such as obstacles from capital difficulties, lack of product innovation, and lack of utilizing information technology in product marketing. The method used to develop software in this study uses the Multimedia Development Life Cycle (MDLC) method in which there are six stages. With the Majalengka Batik Augmented Reality application, the Tourism and Culture Office of Majalengka Regency and batik entrepreneurs can add choices in conducting promotions, utilize information technology and make it easier for the public to obtain information. People who were not previously familiar with Majalengka batik, with this research the community became get to know Majalengka batik. As well as being able to attract people's interest in wearing Majalengka typical batik. Abstrak. Multimedia merupakan produk dari teknologi informasi yang kelebihannya untuk menarik imajinasi serta menarik minat masyarakat, daya tarik ini didukung dengan adanya gambar, suara,teks serta gerakan animasi. Usaha batik mengalami beberapa hambatan seperti hambatan dari kesulitan modal, kurangnya inovasi produk, serta kurangnya dalam memanfaatkan teknologi informasi dalam pemasaran produk.Metode yang digunakan untuk mengembangkan perangkat lunak dalam penelitian ini menggunakan metode Multimedia Development Life Cycle (MDLC) di mana terdapat enam tahapan. Dengan adanya aplikasi Augmented Reality Batik Majalengka, Dinas Pariwisata dan Kebudayaan Kabupaten Majalengka serta para pelaku usaha batik dapat menambah pilihan dalam melakukan promosi, memanfaatkan teknologi informasi dan memudahkan masyarakat dalam mendapatkan informasi.masyarakat yang sebelumnya tidak mengenal batik Majalengka, dengan adanya penelitian ini masyarakat menjadi mengenal batik Majalengka. Serta dapat menarik minat masyarakat untuk mengenakan batik khas Majalengka.